A política de perímetros irrigados e suas implicações nos projetos cearenses Ayres de Souza e Araras Norte - Ximenes, Antonia Vanessa Silva Freire Moraes (2018)
This research presents discussions about the policies of irrigated perimeters and their implications in the Ayres de Souza and Araras Norte projects, located in the municipalities of Sobral and still in Varjota and Reriutaba, respectively. The research of a qualitative nature arises from the need to know the policy of irrigated perimeters and their implications in these projects studied, which, as well as the policy that underlies them, are subject to the changes imposed by the power relations carried out by the capitalist state. Therefore, this research presents as a spatial clipping the areas corresponding to the projects studied and their surroundings, taking as a temporal cut the 1970s, the framework for creating this policy, until the year 2017. Its main objective is to understand these policies of the irrigated perimeters and its implications for projects in Ceará, Ayres de Souza and Araras Norte, with the following specific objectives: a) Present a brief hissory of irrigated perimeter policy; b) Disclose the main characteristics and aspects of the irrigated perimeters Ayres de Souza and Araras Norte; c) Reflect on Ayres de Souza and Araras Norte in the context of irrigated perimeter policy. Thus, the research was based on theoretical and empirical studies, considering also documentary sources and oral hissories as contribution to the understanding of the studied problem, resulting from the political reorientation of irrigated perimeters, which triggered a series of perceived consequences with greater or less intensity in the projects studied and considered in this study because they show the unfolding of this policy, whose trajectory is divided into two distinct phases: the first, paternalistic and assistentialist, and the second, with neoliberal characteristics and directed to the expansionism of agribusiness in the semiarid.